The Effect of Media Exposure, Firm Size, and Leverage on Carbon Emission Disclosure in Energy Companies - Gadis Yesile; Shiwi Angelica Cindiyasari; Yanti Puspita Sari; Marsi Fella Rizki; Imam Ahmad (CV. Kalimasada Group, 2026)
Climate change has become a major global concern, with the energy sector recognized as one of the largest contributors to carbon emissions in Indonesia. This condition has increased demands for greater corporate transparency through carbon emission disclosure as part of sustainable business practices. This study aims to examine the effects of media exposure, firm size, and leverage on carbon emission disclosure among energy companies listed on the Indonesia Stock Exchange during the 2021–2024 period. A quantitative research approach was employed using purposive sampling, resulting in 22 companies with 88 firm-year observations. The data were analyzed using panel data regression with EViews 12. The findings indicate that media exposure has a positive and significant effect on carbon emission disclosure, while firm size and leverage do not have a significant effect. These results suggest that external public pressure through media attention plays a more important role in encouraging corporate transparency than internal company characteristics. This study concludes that media exposure is an important determinant of carbon emission disclosure in Indonesian energy companies. The findings contribute to the environmental accounting literature and provide practical implications for regulators and corporate management in strengthening sustainability reporting and improving transparency in carbon emission disclosure.